2019
DOI: 10.1111/jen.12679
|View full text |Cite
|
Sign up to set email alerts
|

High risk of the fall armyworm invading Japan and the Korean Peninsula via overseas migration

Abstract: The fall armyworm, Spodoptera frugiperda (J.E. Smith), is an invasive pest species in the Old World. This species is originally native to the Americas. Since 2016, S. frugiperda has spread widely and rapidly throughout Africa, the Middle East, India, Southeast Asia and, most recently, to southern China. By May 2019, S. frugiperda had appeared in 13 provinces in southern China and will spread further into northern China. It is highly likely that S. frugiperda will enter Japan and Korea via overseas migrations a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 33 publications
2
33
0
1
Order By: Relevance
“…FAW invasion has become the biggest threat to maize production in sub-Saharan Africa due to its rapid spread to almost all countries in the region and associated crop damage [ 2 ]. The pest has further spread, during the last two years to India [ 3 ], Yemen, Sri Lanka, Bangladesh, Myanmar, Thailand, China [ 4 , 5 , 6 ], Indonesia, Laos, Malaysia, Vietnam, Egypt, the Republic of Korea, and Japan [ 7 ] and the most recent invasions has been detected in Australia, Mauritania, and East Timor [ 8 ]. The impact of FAW on maize yield in Africa has been severe [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…FAW invasion has become the biggest threat to maize production in sub-Saharan Africa due to its rapid spread to almost all countries in the region and associated crop damage [ 2 ]. The pest has further spread, during the last two years to India [ 3 ], Yemen, Sri Lanka, Bangladesh, Myanmar, Thailand, China [ 4 , 5 , 6 ], Indonesia, Laos, Malaysia, Vietnam, Egypt, the Republic of Korea, and Japan [ 7 ] and the most recent invasions has been detected in Australia, Mauritania, and East Timor [ 8 ]. The impact of FAW on maize yield in Africa has been severe [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This pest does not have a diapause phase and hence is only capable of overwintering in warmer climates (van Huis, 1981; CABI, 2020). The fall armyworm can breed in the summer, but cannot survive over winter in the weather conditions of South Korea (Ma et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important is natural pathways due to the pest’s innate ability to fly for long distances either on its own, or in conjunction with the wind, or a combination of those factors (Devorshak, 2012). It was suggested that the fall armyworm could fly from eastern China into southern areas of South Korea due to its own strong flight capacity and wind‐assisted flight, and this pest presents a major threat to maize production in South Korea (Ma et al ., 2019; CABI, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…UGF adalah ngengat yang dapat bermigrasi dan bersifat polifag sehingga resiko penyebarannya sangat tinggi (Goergen et al 2016). Berasal dari wilayah tropis belahan barat Amerika Serikat dan Argentina, UGF kemudian menyebar ke wilayah Afrika dan akhirnya terdeteksi di Asia (Kuate et al 2019;Ma et al 2019). UGF juga dilaporkan sebagai hama utama pada beberapa tanaman kelompok Poaceae lainnya, seperti padi, tebu, gandum, dan sorgum (Yu et al 2003;Goergen et al 2016).…”
Section: Pendahuluanunclassified